2003
DOI: 10.1097/01.asn.0000081664.65772.eb
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Calcifications in Uremic Patients

Abstract: Abstract. Cardiovascular disease is the leading cause of mortality among patients with ESRD (chronic kidney disease stage 5). Left ventricular hypertrophy and arterial diseases are the two principal risk factors for cardiovascular mortality in hemodialysis patients. Epidemiologic studies show that damage to large conduit arteries contributes to morbidity and mortality in patients with chronic kidney disease. Atherosclerosis is primarily an intimal disease characterized by the presence of plaques and occlusive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
138
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(146 citation statements)
references
References 40 publications
3
138
0
5
Order By: Relevance
“…By contrast, AS evaluates VC in muscular (radial and digital) or predominantly muscular (iliac and femoral) arteries, which are more susceptible to the calcification of the media (14,27). Although age, diabetes, and phosphorus levels seemed to be common elements associated with both pathologic KS and AS, this study shows the different prognostic value of both indexes, which suggests that the location of calcification seems to have prognostic significance in patients not on dialysis (28). Although both indexes behaved as predictors of death and hospital admission in the unadjusted analysis, only the AS is confirmed as an independent predictor in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 59%
“…By contrast, AS evaluates VC in muscular (radial and digital) or predominantly muscular (iliac and femoral) arteries, which are more susceptible to the calcification of the media (14,27). Although age, diabetes, and phosphorus levels seemed to be common elements associated with both pathologic KS and AS, this study shows the different prognostic value of both indexes, which suggests that the location of calcification seems to have prognostic significance in patients not on dialysis (28). Although both indexes behaved as predictors of death and hospital admission in the unadjusted analysis, only the AS is confirmed as an independent predictor in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 59%
“…Physiological examination has shown a reduction in the ankle brachial index in patients with vascular stenosis as compared with the exacerbation of the brachial ankle pulse wave velocity in patients with vascular sclerosis. Cardiovascular disease results from both types of calcifications [12]. The mortality rate among patients with CKD-MBD is 10-to 20-fold higher than that among healthy people [13].…”
Section: Discussionmentioning
confidence: 99%
“…(Schwarz et al, 2000). Medial calcification has been shown to affect vascular elasticity and leads to increased arterial wall stiffness of large capacity, elastic-type arteries like the aorta and the common carotid artery, increased pulse pressure and decreased perfusion of coronary arteries during diastole (Blacher et al, 1998;London, 2003;Speer & Giachelli, 2004). Recent studies also demonstrated that elevated FGF23 levels were associated with arterial stiffness, increased left ventricular mass index and increased prevalence of left ventricular hypertrophy in patients with CKD (Hsu & Wu, 2009;Mirza et al, 2009;Gutierrez et al, 2009).…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%